Interactions of Microplastics with Persistent Organic Pollutants and the Ecotoxicological Effects: A Review - Kuok Ho Daniel Tang (Tropical Aquatic and Soil Pollution, 2021)
With the increasing presence of microplastics and persistent organic pollutants (POPs), it is crucial to understand the interactions between the two emerging environmental pollutants and their ecotoxicological risks. This paper reviews more than 50 relevant scholarly papers published mainly in the past 10 years. It shows that the sorption of POPs to microplastics is affected by environmental factors and the properties of microplastics. The environmental factors comprise salinity, pH, natural organic matters and temperature. The properties of microplastics include degree of aging, molecular weight, size, shape, density, crystallinity, polymer type and color. The two factors are interconnected through weathering and weatherability of microplastics, where properties of microplastics, hence their interactions with POPs would be modified by environmental factors. Microplastics are potential vectors of POPs due to their ability to sorb and concentrate POPs. However, the studies reviewed showed the impacts to be low or insignificant and the sorbed POPs do not demonstrate significantly high accumulation, bioavailability and toxicity. In some literature, it has been reported that microplastics might reduce POPs in an organism. Due to limited studies and opposing views, there is a need to conduct more studies involving diverse POPs and microplastics under multiple conditions to provide a more holistic understanding on this subject.